Using an Online Classroom and Artificial Intelligence for the Education of Medical Dispatchers - Čavničar, Boštjan; Golob, Matevž (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The use of online classrooms and artificial intelligence (AI) for the education of medical dispatchers represents a major innovation in the educational process. The integration of AI in online classrooms offers the possibility to personalise learning pathways, tailor content to the needs of individuals and analyse performance, which contributes to better training of medical dispatchers. The article presents the possibilities of online classrooms in the process of training medical dispatchers. Advantages such as flexibility and cost-effectiveness are highlighted alongside challenges such as technological barriers and limited practical application. The article also presents proven methods for successful implementation of the learning process, including curriculum coordination, interactive curriculum, and ongoing user support.